Can mass media be an obstacle to rationing decisions? A case report from Portugal - Costa, Eva Dias (2020)
Purpose Continuous introduction of advanced health technologies coupled with limited resources force governments to adopt rationing measures in all types of health systems. The mass media can influence the application of these measures by rising people and patients' expectations and demands for new forms of healing. This article intends to find evidence of this influence by reporting two recent cases which occurred in Portugal involving two innovative drugs, one for the treatment of hepatitis C and another for type I spinal muscular atrophy. The new drugs were not publicly funded despite promising excellent overall health outcomes because of their high cost and exaggerated burden on national health system (NHS). Design/methodology/approach A qualitative research was used to collect information conveyed by the conventional media and social networks. Findings After a strong dissemination through conventional and social media of the nonapproved treatments, the drugs swiftly garnered support among the public and triggered remarkable and relentless advocacy efforts. The findings of this paper suggest that society opinions and, by extension, the decision of policy-makers are very susceptible to the influence of the mass media. Practical implications New ways of sharing information are changing health research and public health. Social implications These stories raise complex tensions and important questions about resource-allocation decisions involving scientific research or innovative medicine. Societal preferences seem very vulnerable to information conveyed by the mass media. Originality/value This study is the first attempt to awaken attention to the influence that Portuguese mass media may exercise on future healthcare rationing decisions.